UPAYA PENINGKATAN HASIL DAN MOTIVASI BELAJAR IPS MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) - Herlina (Jurnal Ilmu Pendidikan dan Sosial, 2023)
The purpose of this study was to determine the increase in social studies learning outcomes and motivation through the Problem Based Learning (PBL) learning model. The data used in this study are test and non-test results, where the test instruments in this study are pretest, posttest, and multiple choice questions to measure student learning outcomes. the results obtained by the average value of students in the first cycle is equal to 68.89. In cycle II there was an increase, namely, the average student score was 81.19, then in cycle III the average student daily test score increased by 90.23, or as many as 95% of students were declared complete. With the application of Problem Based Learning which is part of an innovative learning model, the role of the teacher as an educator must be able to arouse student learning interest, learning motivation, and student participation in the learning process so that student achievement will increase compared to before which still applies conventional lecture methods.